Cytokeratin 8 is expressed in human corneoconjunctival epithelium, particularly in limbal epithelial cells - Merjava, Stanislava; Brejchova, Kristyna; Vernon, Amanda; Daniels, Julie T; Jirsova, Katerina (Investigative ophthalmology & visual science, 2011)
PURPOSE: The purpose of this study was to investigate the expression of cytokeratin (CK) 8 in the corneoconjunctival epithelium. METHODS: In 17 cadaveric corneoscleral discs and 3 other discs, the presence of CK8 alone or CK8, together with CK3, CK15, vimentin, and integrin α6, was investigated by using indirect immunohistochemistry on radial cryosections. Four corneoscleral discs stored in organ culture were used for the preparation of tangential sections of the limbus and for the isolation of limbal epithelial cells and their subsequent cultivation. CK8 expression was examined by RT-PCR in the corneal, limbal, and conjunctival epithelium. RESULTS: Sixty percent of the cadaveric corneoscleral samples and all samples stored in organ culture revealed positivity for CK8 in the basal epithelial layer of the limbus. Positive basal cells formed a single line or separated clusters. The signal for CK8 became weaker toward the surface of the limbal epithelium. The colocalization of CK8 with vimentin and CK15 in the limbus was also found. CK3 showed only occasional positivity in some of the surface limbal cells. The expression of integrin α6 in the basal membrane was absent or decreased under the CK8-positive clusters. Cell cultures revealed strong positivity for CK8 in approximately 80% of the cultured cells, and CK8 expression in the cornea, limbus, and conjunctiva was determined by RT-PCR. CONCLUSIONS: The study demonstrates the strong expression of CK8 in limbal epithelial basal cells, which is maintained during the differentiation and migration of the limbal cells toward the central corneal epithelium.
Keywords: fluorescenční protilátková technika nepřímá; exprese genu; Gene Expression; RNA, Messenger; orgánové kultury - kultivační techniky; epitelové buňky; Conjunctiva; fluorescenční mikroskopie; keratin-3; Adolescent; Epithelium, Corneal; Epithelial Cells; keratin-8; Adult; buněčné kultury; Integrin alpha6; vimentin; konjunktiva; Aged; dospělí; Keratin-8; senioři; Fluorescent Antibody Technique, Indirect; messenger RNA; Organ Culture Techniques; polymerázová řetězová reakce s reverzní transkripcí; Keratin-3; mladiství; Limbus Corneae; senioři nad 80 let; lidé; Keratin-15; Microscopy, Fluorescence; keratin-15; integrin alfa6; Humans; Cell Culture Techniques; Aged, 80 and over; Reverse Transcriptase Polymerase Chain Reaction; lidé středního věku; limbus corneae; Vimentin; Middle Aged; rohovkový epitel